2005
DOI: 10.1021/jp052214e
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Ultrasmall Si Nanoparticles Prepared through Electrochemical Dispersion of Bulk Si

Abstract: Studying the properties and stability of silicon nanoparticles (Si-np) in aqueous environments may lead to novel applications in biological systems. In this work, we use absorption and photoluminescence (PL) spectroscopy to characterize ultrasmall Si-np prepared through anodic etching and ultrasonic fractionation of a crystalline Si wafer. Their behavior is studied over time in 2-propanol and during treatments with water, NaOH, HCl, and H 2 O 2 . The observed population is divided into two types of material: b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 62 publications
2
27
0
1
Order By: Relevance
“…8b). Previous studies on silica have suggested that the fluorescence sources in the UV-B range are nanosized hydrogen-passivated silica species [54]. During the synthesis of our samples, similar species could be obtained along with the prevalent 1.1 lm (for SiO 2 -FD) and 1.2 lm (for SiO 2 -HD) particles identified by DLS.…”
Section: Characterisation Of G Hirsutum Loaded Silicasupporting
confidence: 74%
“…8b). Previous studies on silica have suggested that the fluorescence sources in the UV-B range are nanosized hydrogen-passivated silica species [54]. During the synthesis of our samples, similar species could be obtained along with the prevalent 1.1 lm (for SiO 2 -FD) and 1.2 lm (for SiO 2 -HD) particles identified by DLS.…”
Section: Characterisation Of G Hirsutum Loaded Silicasupporting
confidence: 74%
“…26 Researchers have developed many routes for preparing organically functionalized Si-np. However, the products have been generally limited to aliphatic surface chemistries stable only in nonpolar organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 In a recent work, we reported similar, but much more substantial increases in redshifted PL after treatment of unmodified Si-np-H with NaOH under nearly identical conditions to the base hydrolysis. 26 The results were attributed to oxidation of the nanoparticle surface with possible formation of Si-O-Si bridge structures. Note that the relative lack of redshifted PL for the H 2 O fraction suggests that the carboxyl modification provides some additional protection against surface oxidation.…”
mentioning
confidence: 99%
“…The red-tail emissions at 335 nm and greater were much more prominent after aqueous treatments and have been attributed to various species of oxidized and aggregated material. 12 The carboxyl functionalized Si-np-COOH were prepared via hydrosilylation of the Si-np-H with the bi-functional ester methyl 4-pentenoate, CH 2 = CHCH 2 CH 2 C͑O͒OCH 3 . 10 The reaction proceeds with insertion of the alkene into a thermally activated Si-H bond to form a stable Si-C linkage with the ester exposed to the solvent.…”
mentioning
confidence: 99%